Community Perceptions on Urban Forests Development in Riparian Areas of Cisadane River, South Tangerang City - Urfi Izzati; Hayati Sari Hasibuan (Jurnal Ilmu Kehutanan, 2023)
The continuous decrease in green open spaces due to urban development leads to harmful environmental problems for communities. Land scarcity is one of the significant reasons for the difficulty in urban forest development in riparian areas. The development of riparian urban forests serves a dual purpose, namely preserving the natural riparian function for vegetation and increasing the green open space area size. Therefore, this study aimed to analyze the riverside community's understanding and views on urban forests and their perceptions of riparian urban forest development. Data were collected through questionnaires and interviews and analyzed using descriptive statistics. Approximately 63.64% and 96.97% of the respondents understood and viewed the urban forests well. Furthermore, 90.91% of the respondents agreed with the riparian urban forest development. Generally, 66.67% agreed to create greener, tidier, cleaner, and more beautiful riparian areas to attract tourists. The positive perception of the community regarding the urban forest development in riparian areas became a rational basis to sustain its function and increase the size of urban forests and green open space areas.